The Role of Sharia Supervisory Board in Implementing Public Trust on Sharia Banks - Illa Susilawati; Lutfi Madani; Sutrisno Sutrisno; Arim Nasim; Caria Ningsih (Islamic Research, 2023)
This study aims to see how implementing the Sharia Supervisory Board and its impact on providing public trust in Islamic banks. This study uses a quantitative approach with the method of Systematic Literature Review from various journals. With the Systematic Literature Review method, the research identifies all empirical evidence, where the identification aims to answer questions such as "What is the role of the sharia supervisory board on public trust?", "Implementation of the sharia supervisory board on sharia banking?". The analysis results found that the Sharia Representative Council (DPS) has a high level of helping to attract public interest. This is because the higher the spread of DPS, the public's knowledge about banking sharia will be increasingly known. This finding shows that Sharia Supervisory Board plays an essential role in providing public confidence to be interested in being part of a sharia bank because, so far, there are known factors that attract the public in the form of external factors such as marketing factors, psychological factors, cultural factors, social factors, and social factors. Personality so that this can be used as a view for further research that the Sharia Representative Council also still plays an essential role in contributing to society.